1979
DOI: 10.1295/polymj.11.665
|View full text |Cite
|
Sign up to set email alerts
|

Dilute-Solution Behavior of a Rigid Polymer, Poly[trans-bis(tributylphosphine)platinum 1,4-butadiynediyl]

Abstract: ABSTRACT:Poly[trans-bis(tributylphosphine)platinum I ,4-butadiynediyl] (PPBD) in heptane at 25cC was studied by viscosity and sedimentation velocity measurements over a range of weightaverage molecular weight Mw from 7 x 10 3 to 1.4 x 10 5 Although the chemical structure of PPBD suggests a very rigid nature of the chain, the measured value 1.1 for the exponent in the Mark-Houwink-Sakurada [IJ] (intrinsic viscosity)-Mw relation indicated an appreciable flexibility of the chain. The data for [IJ] and sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The intrinsic viscosities of this and related polymers, [η] = 1.19−1.25, were found to be independent of the nature of the solvent, and the solubility parameter δ was found to be in the range of 6.6−9.7 (cal/mL) 1/2 . , In addition, the α-value in the Mark−Houwink equation (ca. 1.7) was also determined and indicates that this type of polymer has a stiff rodlike structure in solution. , However, it is worth noting that subsequent studies on the same polymer by Fujita and Tabata and their co-workers suggested that the polymer chain is more flexible and can be best represented by a wormlike model.…”
Section: Iii13 Polymer Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…The intrinsic viscosities of this and related polymers, [η] = 1.19−1.25, were found to be independent of the nature of the solvent, and the solubility parameter δ was found to be in the range of 6.6−9.7 (cal/mL) 1/2 . , In addition, the α-value in the Mark−Houwink equation (ca. 1.7) was also determined and indicates that this type of polymer has a stiff rodlike structure in solution. , However, it is worth noting that subsequent studies on the same polymer by Fujita and Tabata and their co-workers suggested that the polymer chain is more flexible and can be best represented by a wormlike model.…”
Section: Iii13 Polymer Propertiesmentioning
confidence: 88%
“…1.7) was also determined and indicates that this type of polymer has a stiff rodlike structure in solution. 172,174 However, it is worth noting that subsequent studies on the same polymer by Fujita 218 and Tabata 219 and their co-workers suggested that the polymer chain is more flexible and can be best represented by a wormlike model.…”
Section: Iii13 Polymer Propertiesmentioning
confidence: 99%
“…The linear extrapolation of the data shown in Figure to p = 1 seems to give a value of k ‘ HI that is consistent with those theoretical values.
3 Axial ratio dependence of k ‘ HI for various solutions of nearly rodlike polymers with N ≲ 0.8; (□) PHIC−DCM; (○) PHIC−toluene; (·) PHIC− n -butyl chloride; (⊡) schizophyllan−water; , (▵) xanthan−0.1 M aqueous NaCl; , (⊙) poly(γ-benzyl l -glutamate)−dimethylformamide; (◇) poly[ trans -bis(tributylphosphine)platinum 1,4-butadiynediyl]−heptane; (▴) poly(terephthalamide- p -benzohydrazide)−dimethyl sulfoxide
…”
Section: K‘ei Vs K‘himentioning
confidence: 99%
“…Following our previous treatment, 10 we compare these experimental S-vP plots with those calculated from the Flory-Ronca lattice theory.11 In consideration of the chain flexibility, theoretical calculations for poly(yne)-platinum polymers were carried out on the basis of the Kuhn-chain assumption, 12 the axial ratio of the Kuhn segment xk being estimated to be 22 from the persistence length an~ the diameter of the polymer. 2 The variations of S in the anisotropic phase are illustrated by the solid curves, and the broken curves indicate the results of calculations extended over the concentration range where the biphasic equilibrium should be expected. The values of S at the boundary between these curves define Scrit· Afthough the theory predicts approximately acceptable values for the isotropic-anisotropic phase equilibrium concentration (vp), a large difference is demonstrated between the calculated and observed order parameters (S).…”
Section: Orientational Ordering In the Liquid Crystalline Statementioning
confidence: 86%
“…Fujita, Teramoto et al 2 have reported solution properties of poly[trans-bis(tri-nbutylphosphine )platinum 1, 4-butadiynediyl] f Pt(PBU3b-C=C-c=ct…”
mentioning
confidence: 99%